2020
DOI: 10.3389/fcimb.2020.594063
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate-Binding Proteins Are Critical for Effective Control of Francisella tularensis Strains in a Mouse Co-Culture System of Adaptive Immunity

Abstract: Francisella tularensis is a Select Agent that causes the severe disease tularemia in humans and many animal species. The bacterium demonstrates rapid intracellular replication, however, macrophages can control its replication if primed and activation with IFN-γ is known to be essential, although alone not sufficient, to mediate such control. To further investigate the mechanisms that control intracellular F. tularensis replication, an in vitro co-culture system was utilized containing splenocytes obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Consequently, S. flexneri escapes from GBPs-mediated growth restriction (14,15,21). Francisella tularensis, the agent of tularemia, is another professional cytosolic Gramnegative pathogen that escapes GBP-mediated growth restriction although to different extents depending on the subspecies considered (16,29). F. tularensis can infect a large number of host cells but has a particular tropism for phagocytic cells, including macrophages (30).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, S. flexneri escapes from GBPs-mediated growth restriction (14,15,21). Francisella tularensis, the agent of tularemia, is another professional cytosolic Gramnegative pathogen that escapes GBP-mediated growth restriction although to different extents depending on the subspecies considered (16,29). F. tularensis can infect a large number of host cells but has a particular tropism for phagocytic cells, including macrophages (30).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, S. flexneri escapes from GBPs-mediated growth restriction (14, 15, 21). Francisella tularensis, the agent of tularemia, is another professional cytosolic Gram-negative pathogen that escapes GBP-mediated growth restriction although to different extents depending on the subspecies considered (16, 29). F. tularensis can infect a large number of host cells but has a particular tropism for phagocytic cells, including macrophages (30).…”
Section: Introductionmentioning
confidence: 99%
“…This was first demonstrated for the closely related bacterium F. novicida and subsequently also for the LVS strain using infection of mononuclear cells; however, control of the highly virulent SCHU S4 strain was not observed in the model ( 48 ). Later, it was demonstrated that control of infection with each of the three F. tularensis strains occurred in a mouse co-culture model, but, again, control was critically dependent on GBPs ( 49 ). Thus, the evidence from animal models indicate that the control of highly virulent strains is distinct from that of attenuated F. tularensis strains and demonstrates that the use of such strains in the models is necessary to identify relevant correlates of immunity and protection.…”
Section: Discussionmentioning
confidence: 99%